Topology optimization of hyperelastic structure based on a directly coupled finite element and element-free Galerkin method. (September 2018) - Zhang, Yaqing; Ge, Wenjie; Zhang, Yonghong; Zhao, Zhenfei; Zhang, Jinwang
Highlights: Meshless-based topology optimization for hyperelastic structures. Adaptive directly coupled FE–EFG method to reduce computational cost. Interpolation scheme for nonlinear structural analysis. Very large deformation and low time cost of this method. Abstract: Meshless methods can solve large classes of problems where grid-based methods are awkward to handle, such as the discretizing of complicated structures, the remeshing in large displacement problems and so on. In this study, a meshless-based topology optimization is proposed for large displacement problems of nonlinear hyperelastic structure. In order to circumvent nonlinear numerical instabilities, the linear and nonlinear analyses are set in the low- and high-stiffness region, respectively. Thus, an interpolation scheme is adopted for hybridizing the linearity and nonlinearity in the structure analysis. A directly coupled finite element and meshless method is introduced to reduce the computational cost of meshless methods and an auto-coupling strategy is proposed for the adaptive arrangement of finite element and meshless regions. Several numerical examples are given to demonstrate the effectiveness of the proposed method.